2011
DOI: 10.1111/j.1468-2958.2011.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation in Couples' Communication About Weight Management: An Analysis of How Both Partners Contribute to Individuals' Health Behaviors and Conversational Outcomes

Abstract: Using confirmation theory, this study investigated how romantic couples' (N = 100) accepting and challenging communication was associated with several weight management (WM) outcomes (i.e., partners' general effectiveness in motivating each other to enact healthy behaviors, productivity of WM conversations, and diet and exercise behaviors). Actor-partner interdependence model analyses showed that acceptance and challenge from partners simultaneously predicted how effective partners were in motivating healthy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 41 publications
3
46
1
Order By: Relevance
“…This finding is consistent with the indirect effects models and with the literature indicating that people in harmonious relationships perceive greater positive social influence from the partner (Markey et al, 2007). Together these findings reinforce that people's perception of their partners' health communication is important to consider in conjunction with their relationship satisfaction (Markey et al, 2007) and their health communication (Dailey, Romo, & Thompson, 2011). However, this study builds upon the previous research by identifying how positive and negative social control are distinctly associated with their relationship satisfaction.…”
Section: Social Control and Relationship Qualitysupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is consistent with the indirect effects models and with the literature indicating that people in harmonious relationships perceive greater positive social influence from the partner (Markey et al, 2007). Together these findings reinforce that people's perception of their partners' health communication is important to consider in conjunction with their relationship satisfaction (Markey et al, 2007) and their health communication (Dailey, Romo, & Thompson, 2011). However, this study builds upon the previous research by identifying how positive and negative social control are distinctly associated with their relationship satisfaction.…”
Section: Social Control and Relationship Qualitysupporting
confidence: 80%
“…Indeed, Dailey, Romo, and Thompson (2011) found that people's satisfaction with weight management conversations is positively related to their perception of acceptance messages (e.g., warmth, care, and positivity) from the partner. When both partners perceived low-challenge messages (e.g., push to be healthier) from each other, they were the most satisfied with the weight management conversation (and vice versa).…”
Section: Health Influence Perceptions and Relationship Qualitymentioning
confidence: 99%
“…The findings from this study provide further evidence to support the view that it may be more appropriate and effective to focus on healthy eating and exercise in pregnancy, rather than on GWG (Smith et al, 2015). It has been demonstrated elsewhere that partners can help one another manage their weight (Dailey et al, 2011), and this could be investigated in the context of providing support for healthy eating in pregnancy.…”
Section: Discussionsupporting
confidence: 61%
“…Of the 47 studies, 36 used quantitative study designs , nine used qualitative designs and two used a combination of these methods .…”
Section: Methodsmentioning
confidence: 99%
“…Some studies identified factors that influence body size management or estimated the relative incidence of various stages of change in the managing process. Many quantitative studies investigated socio‐demographic differences in body size perceptions .…”
Section: Methodsmentioning
confidence: 99%